THE IMPLEMENTATION OF PROJECT BASED LEARNING IN IMPROVING READING COMPREHENSION OF THE ELEVENTH GRADE STUDENTS OF SMA NEGERI 2 SIGI - Fitriani, Fitriani; Rofiqoh, Rofiqoh; Dewi, Anjar Kusuma; Mukrim, Mukrim (Tadulako University, 2024)
The objective of this research is to prove whether the implementation of Project Based Learning (PjBL) can improve reading comprehension of the eleventh-grade students of SMA Negeri 2 Sigi. This research used a quasi-experimental research design that consisted of two groups: an experimental and control groups. The sample was selected using a purposive sampling technique. The sample of this research was 58 eleventh-grade students of SMA Negeri 2 Sigi, 28 students from class XI IPA 2 as the experimental group, and 30 students from class XI IPA 1 as the control group. The data were collected through pre-test and post-test. Data were analyzed using a t-test to compare the experimental and control groups' pre-test and post-test mean scores. The mean score pre-test for the experimental group was 63.93 and the control group was 66.58. Then, the mean score of the students' post-test score for the experimental group was 74.73, and the control group was 71.33. By applying 0.05, level of significance, it is found that the t-counted value (4.56) is higher than the t-table value (1.673). Therefore, the research hypothesis is accepted. This result indicates that the implementation of PjBL in this study effectively improved the students’ reading comprehension. The implication of these findings is that in teaching reading, teachers can apply the PjBL method during the teaching and learning process as one of the effective methods to improve students' reading comprehension.